Respuesta :
Answer:
The correct answer to the following question will be "[tex]\mu_{s}=\frac{T_{m}Cos\theta}{M_{g}-T_{m}Sin\theta}[/tex]".
Explanation:
According to the question,
[tex]\sum F_{x}[/tex]
⇒ [tex]TCos \theta-F_{s}=0[/tex]
⇒ [tex]T_{m}Cos \theta =F_{s}[/tex] ...(equation 1)
[tex]\sum F_{y}[/tex]
⇒ [tex]TSin \theta+F_{N}=m_{g}[/tex]
⇒ [tex]M_{g}-TSin \theta=F_{N}[/tex] ...(equation 2)
Now,
From equation 1 and equation 2, we get
⇒ [tex]T_{m} Cos \theta = \mu_{s}F_{N}[/tex]
On putting the value of [tex]F_{N}[/tex], we get
⇒ [tex]T_{m} Cos\theta = \mu_{s}(M_{g}-T_{m}Sin \theta)[/tex]
⇒ [tex]\mu_{s}=\frac{T_{m}Cos\theta}{M_{g}-T_{m}Sin\theta}[/tex]
The coefficient of static friction between the floor and the box is [tex]\mu_s = \frac{T_mCos\theta}{M_9-T_mSin\theta^n}[/tex]
Coefficient of static friction:
Static friction should be the force where an object should be at rest. It is the friction where the individuals try to shift a stationary object on a surface, without triggering any motion that lies between the body and the surface.
Since
[tex]\sum F_x[/tex] should be
T Cosθ - F_s =
Now
T_mCosθ = F_s ..........(equation 1)
Now
[tex]\sum F_y[/tex]
T Sinθ + F_N = m_g
M_g - TSinθ = F_N............(equation 2)
Now
T_mCosθ = \mu_s F_N
Now
T_mCos\mu = \mu(M_g - T_mSinθ)
So, [tex]\mu_s = \frac{T_mCos\theta}{M_9-T_mSin\theta^n}[/tex]
Hence, The coefficient of static friction between the floor and the box is [tex]\mu_s = \frac{T_mCos\theta}{M_9-T_mSin\theta^n}[/tex]
Learn more about friction here: https://brainly.com/question/18519949